Theatre practice in French classes in qualifying secondary school: an incubator for soft skills - YAHYAOUI , My Ahmed; BOURHT , Hajar (Revue Internationale du Chercheur, 2025)
Abstract At the dawn of the third millennium, in a global context marked by the increasing orientation of education systems towards the essential skills of the 21st century, in particular ‘soft skills’, the Moroccan education system has undertaken far-reaching reforms. These are embodied in the ‘Strategic Vision 2015-2030’ and ‘Framework Law 51.17’, which emphasise the importance of transversal, ‘soft’ or ‘non-technical’ skills. These strategic frameworks require education players to move towards innovative teaching practices that focus on developing these skills. Faced with the deficits identified in the OECD report (2022), the aim of this study is to explore the potential of theatrical practices in the teaching-learning of French at qualifying secondary level, in order to strengthen 21st century skills while linking them with disciplinary skills. Adopting a qualitative approach, the research focuses on four key skills defined by Lamri (2018) - communication, creative thinking, critical thinking and cooperation - analysing them from two angles: their integration into ‘actor training’ and ‘pedagogical orientations’. The perceptions of teachers are also examined through a representative sample. This study proposes an innovative vision, summarised by the ‘4C+’ model, aimed at harmoniously integrating these skills into educational practices.